2022
DOI: 10.1177/02704676221080919
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Images: Media Use and Public Opinion About Gene Editing

Abstract: As gene editing technologies such as CRISPR have become increasingly prominent, so have media portrayals of them. With this in mind, the present study builds on theoretical accounts of framing effects, cultivation effects, and genre-specific viewing effects to examine how different forms of media use predict attitudes toward applications of gene editing. Specifically, the study tests how news use, overall television viewing, and science fiction viewing are related to such attitudes. The analyses draw on origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The media serves as a bridge between complex scientific concepts and the general public, translating these ideas into more digestible information. A recent study by Dawson et al (2022) offers valuable insights into this issue. They found that favorable media coverage can significantly foster public support for the use of CRISPR.…”
Section: Previewmentioning
confidence: 99%
“…The media serves as a bridge between complex scientific concepts and the general public, translating these ideas into more digestible information. A recent study by Dawson et al (2022) offers valuable insights into this issue. They found that favorable media coverage can significantly foster public support for the use of CRISPR.…”
Section: Previewmentioning
confidence: 99%
“…Further, one study showed that science fiction programming had almost no association with attitudes on its own, but was associated with television science news use, which in turn was associated with positive attitudes toward science [Brossard & Dudo, 2012]. Another study also showed a nonsignificant relationship between watching science fiction and support for using gene editing [Dawson, Paintsil, Bingaman & Brewer, 2022].…”
Section: Effects Of Cultivationmentioning
confidence: 99%